KARELIAN LANGUAGE IN THE EDUCATIONAL SYSTEM IN REPUBLIC OF KARELIA - Svetlana Viktorovna Kovaleva; Aleksandra Pavlovna Rodionova (Science and Innovation Center Publishing House, 2013)
The paper focuses on the study of the situation of teaching of the Karelian language in light of contemporary language policy. Education is a sphere of regimented communication regulated by administrative and governmental authorities. The regulation is targeted at orderly use of language in the society, and is effected by means of language legislation. The process to revitalize the Karelian language was initiated by the resolution of the conference “Karelians“ in 1989. In the academic year 2010/2011 the Karelian language was taught in 11 districts (Belomorsky, Kemsky, Kalevalsky, Kondopozhsky, Louhsky, Medvezhjegorsky, Muezersky, Olonetsky, Prionezhsky, Pryazhinsky, and Suojarvsky) and two municipalities (Petrozavodsk and Kostomuksha). The Karelian language is taught also in institutions for extra-curricular education. In 2011, 48 children studied Karelian proper and 43 children – the Olonetsian dialect in such institutions. Thus, the situation with the Karelian language in education today does not look bright at all. Schoolchildren are not motivated to study the Karelian language as it is unlikely to bring any “bonuses” in education, finding a job or further socialization. Furthermore, placement of Karelian language students is very problematic. Although the Karelian language does function in education – one of the spheres maintaining the language vitality –in the situation where the Russian language dominates in most major spheres of communication the real-life social status of the Karelian language is such that there is no potential for “building up” the communicative load of the newly scripted Karelian language and widening its functionality.DOI: http://dx.doi.org/10.12731/2218-7405-2013-7-21